WILSON'S DISEASE IN IRELAND: INCREASING PREVALENCE OVER 40 YEARS. (29th November 2012) - O'Brien, M; Kinsella, K; Reilly, M; Sweeney, B; Walsh, C; Hutchinson, M
Abstract : Wilson's disease is an autosomal recessive disorder of copper transport caused by mutations in the ATP7B gene located on chromosome 13. Estimates of population prevalence range from 18 to 30 cases per million, however, the CI s are broad. Epidemiological studies of Wilson's disease are limited. We undertook a population based study of Wilson's disease in the Republic of Ireland covering the years 1971–2011 and using data from our previous study in 1991. Prevalence and true prevalence were calculated at multiple time points to coincide with census years. Fifty cases of Wilson's disease were ascertained between 1971 and 2011. The mean age at diagnosis was 20 years, with an average time delay to definitive diagnosis of 24 months. At presentation, hepatic symptoms were predominant (39%), followed by mixed symptoms (hepatic and neuropsychiatric) (31%) and neuropsychiatric symptoms (25%). Prevalence increased every year from 0 cases per million in 1971 to nine cases per million in 2011. True prevalence for the same periods was 6.7/million in 1971, 4.9/million in 1981, 9.9/million in 1991, and 8.9/million in 2011. The rise in the true prevalence of Wilson's disease over the 40 year (1971–2011) interval may reflect improved diagnostic methods, in particular the use of MRI, and improved survival due to earlier diagnosis.